Theoretical Analysis of Mining Induced Overburden Subsidence Boundary with the Horizontal Coal Seam Mining - Weitao Yan; Junjie Chen; Yi Tan; Wenzhi Zhang; Lailiang Cai (Advances in Civil Engineering)
The overburden subsidence induced by underground mining has caused great damage to the ecological environmental and seriously threatens the safe use of underground structures. Focusing on the overburden subsidence, this paper uses theoretical analysis method to study the overburden subsidence boundary with a horizontal coal seam mining. In this paper, the viscoelastic theory and the random medium theory are used separately to deduce and analyze the subsidence boundary of bedrock and unconsolidated stratum, which are two media with different lithology. For bedrock, the results show that the subsidence boundary of bedrock is 1/4 of the wavelength of pressure wave from the mining boundary, strata subsidence boundary expands with the increase of vertical distance between calculated strata and coal seam, and the subsidence boundary in bedrock is an upward concave curve. For unconsolidated stratum, the results show that the larger the internal friction angle, the greater the angle between subsidence boundary and horizontal line. From the bottom to the surface of the unconsolidated stratum, the internal friction angle decreases gradually and the angle between subsidence boundary and horizontal line also decreases gradually, so the subsidence boundary curve in the unconsolidated stratum is convex. Combined with the bedrock and unconsolidated stratum, it is concluded that the subsidence boundary of the whole overburden is bowl-shaped. This study is helpful to reveal the black box of rock subsidence and can provide theoretical support for the establishment of overburden subsidence prediction model and transparent mine in the later stage.